Sinus bradycardia in children - T. K. Kruchina; G. A. Novik (Лечащий Врач)
Sinus bradycardia is common in children, especially in adolescent period. Tactics of management and treatment of children with bradycardia is defined by presence of cardiovascular pathology, clinical manifestations of the disease, stability and pronouncement of the arrhythmia, efficiency of the drug therapy. If there is a symptom of sick sinus syndrome in a child, we put the question about permanent pacemaker, according to national and international recommendations.